2015
DOI: 10.11648/j.ijgg.20150305.13
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6: A Proinflammatory Role in Nephritis in Patients with Systemic Lupus Erythematosus

Abstract: Background. Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with a common finding of renal involvement which is related to high incidence of mortality and morbidity. IL-6 is produced by leukocytes and intrinsic kidney cells that affects inflammation, increases mesangial cell proliferation, and also contributes to autoimmunity. Objective. To detect the serum level as well as expression in PBMCs in the blood of IL-6 in SLE patients. Furthermore we compare serum level, as well as expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The elevated serum IL-6 levels and its mRNA expression was reported in SLE patients as well as in lupus nephritis patients. 7 Earlier studies have demonstrated that the urinary excretion of IL-6 is significantly higher in active lupus than inactive lupus patients and the healthy control group. 41 Similarly, an elevated level of serum IL-6 was established in SLE patients and also correlated with disease activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The elevated serum IL-6 levels and its mRNA expression was reported in SLE patients as well as in lupus nephritis patients. 7 Earlier studies have demonstrated that the urinary excretion of IL-6 is significantly higher in active lupus than inactive lupus patients and the healthy control group. 41 Similarly, an elevated level of serum IL-6 was established in SLE patients and also correlated with disease activity.…”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5] The cytokines such as B-lymphocytic stimulator, interferon-a, TNF-a, interleukin (IL)-6, IL-2, IL-17 and IL-10 are implicated in SLE pathogenesis. 6,7 Among these, IL-6 has an exceptional role as an inflammatory regulator and has a direct role in controlling autoantibody production. 8,9 IL-6 is a multifunctional pro-inflamatory cytokine which acts on various types of cells and is a key stimulator of acute-phase proteins such as CRP, SAA, fibrinogen, haptoglobin, hemopexin, hepcidin and a 1 -antichymotrypsin whereas it reduces the synthesis of albumin in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%